2022
DOI: 10.1186/s40359-022-00897-3
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety among online learning students during the COVID-19 pandemic: a cross-sectional survey in Rio de Janeiro, Brazil

Abstract: Background The COVID-19 pandemic introduced a global need to explore the potential and challenges of online education. Objective To evaluate the presence of depression and anxiety in university students and their level of satisfaction with online learning during the period of social isolation caused by the COVID-19 pandemic. Method A cross-sectional design was used to evaluate 152 online learning stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 24 publications
5
38
1
4
Order By: Relevance
“…Therefore, it could be concluded that instructional factors affected preadolescent learners' online learning anxiety. The results of the study confirm the effects of changes in the learning environment on education as seen in the previous studies (e.g., Abdelwahed et al, 2022;Alshammari et al, 2022;Holubnycha et al, 2021;Pelucio et al, 2022). The current study also shows that learning content is the factor that affected students' online learning anxiety.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, it could be concluded that instructional factors affected preadolescent learners' online learning anxiety. The results of the study confirm the effects of changes in the learning environment on education as seen in the previous studies (e.g., Abdelwahed et al, 2022;Alshammari et al, 2022;Holubnycha et al, 2021;Pelucio et al, 2022). The current study also shows that learning content is the factor that affected students' online learning anxiety.…”
Section: Discussionsupporting
confidence: 90%
“…As online learning during the COVID-19 pandemic could make learners anxious, studies have been conducted to investigate learners' anxiety during the situation (e.g., Abdelwahed et al, 2022;Alshammari et al, 2022;Holubnycha et al, 2021;Pelucio et al 2022). In detail, Abdelwahed et al (2022) found that lack of time and support, technical problems, and lack of technical skills are factors affecting learners' stress and anxiety in online learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result demonstrated that online learning anxiety is negatively related to online learning satisfaction; hence H2 is supported. This finding is aligned with past studies which tested similar variables (Abdous, 2021;Bolliger & Haluga, 2012;Pelucio et al, 2022). Some students still struggle with using technology for learning (Saade et al, 2017).…”
Section: Online Learning Anxiety and Online Learning Satisfactionsupporting
confidence: 90%
“…In the report published by the Organization for Economic Co-operation and Development (OECD) in 2021, it was reported that intervention support programs prepared to prevent increasing mental problems in young individuals during the COVID-19 pandemic, were effective [ 51 , 53 ]. Similarly, it has been emphasized in studies that cognitive and emotional programs should be developed and implemented for particularly vulnerable individuals [ 50 , 51 , 54 , 55 , 56 ]. Research also reveals that interventions to protect and improve mental health have become mandatory, both during and after the pandemic [ 49 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%